2005
DOI: 10.1007/s00232-005-0736-9
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Aquaporin-5 Water Channel in Osmoregulation in Parotid Secretory Granules

Abstract: Aquaporins (AQPs) are a family of channel proteins that allow water or very small solutes to pass, functioning in tissues where the rapid and regulated transport of fluid is necessary, such as the kidney, lung, and salivary glands. Aquaporin-5 (AQP5) has been demonstrated to localize on the luminal surface of the acinar cells of the salivary glands. In this paper, we investigated the expression and function of AQP5 in the secretory granules of the rat parotid gland. AQP5 was detected in the secretory granule m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
4

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 36 publications
0
37
0
4
Order By: Relevance
“…While several AQPs have been localized to intracellular vesicles, including AQP1 (Cho et al, 2002), AQP5 (Matsuki et al, 2005), AQP6 (Yasui et al, 1999), AQP10 (Li et al, 2005) and AQP12 (Itoh et al, 2005), there is no evidence of either AQP3 or AQP4 in vesicle membranes. The detection of these two AQPs in the slime gland may indicate their role in vesicle rupture, but we acknowledge that the slime gland contains several cell types, including an epithelial cell layer.…”
Section: Sus Scrofa Aqp6 [Acc66198]mentioning
confidence: 99%
See 2 more Smart Citations
“…While several AQPs have been localized to intracellular vesicles, including AQP1 (Cho et al, 2002), AQP5 (Matsuki et al, 2005), AQP6 (Yasui et al, 1999), AQP10 (Li et al, 2005) and AQP12 (Itoh et al, 2005), there is no evidence of either AQP3 or AQP4 in vesicle membranes. The detection of these two AQPs in the slime gland may indicate their role in vesicle rupture, but we acknowledge that the slime gland contains several cell types, including an epithelial cell layer.…”
Section: Sus Scrofa Aqp6 [Acc66198]mentioning
confidence: 99%
“…AQPs have been found in secretory vesicles, and are thought to assist vesicle swelling and product release in many cases such as secretory vesicles in human small intestine (Li et al, 2005), rat parotid gland secretory vesicles (Matsuki et al, 2005) and zymogen granules of pancreatic acinar cells (Cho et al, 2002;Itoh et al, 2005). While several AQPs have been localized to intracellular vesicles, including AQP1 (Cho et al, 2002), AQP5 (Matsuki et al, 2005), AQP6 (Yasui et al, 1999), AQP10 (Li et al, 2005) and AQP12 (Itoh et al, 2005), there is no evidence of either AQP3 or AQP4 in vesicle membranes.…”
Section: Sus Scrofa Aqp6 [Acc66198]mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, AQP5 is expressed in the APM, the lateral membrane, and intracellular organelles, but not in the basilar membrane of salivary gland cells (20,21). AQP5 is also present in zymogen granules in rat parotid glands (22). AQP5 mRNA is abundantly present in rat serous acinar cells of exocrine glands such as the parotid and submandibular glands, lacrimal glands, and subepithelial glands of the upper airway, and eye, but not in kidney, brain, or intestine (23).…”
Section: Aquaporin Water Channel Proteins In Salivary Glandsmentioning
confidence: 99%
“…AQP8 may be a genuine ZG membrane protein, however a contamination by mitochondria cannot be ruled out, which express AQP8 as well (16,61). Swelling assays of secretory granules and immunological studies have suggested that AQP5 and AQP6 mediate osmotic swelling of isolated parotid secretory granules suspended in isoosmotic KCl solutions (72,74), but the presence of AQP5 in parotid granules has also been contested using various immunological techniques (75).…”
Section: Channels H 2 O Channelsmentioning
confidence: 99%